Breaking the silence: how social media campaigns shape public awareness of child sexual violence in Indonesia - Yudhi Ade Putra Siregar; Roudotul Jannah; Wikha Azzahra Yunindya; Amia Luthfia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Child sexual abuse (CSA) is a serious public health issue in Indonesia. Although social media campaigns are increasingly being used as a strategy to prevent CSA, evidence regarding their effectiveness remains fragmented and inconsistent, particularly regarding the campaigns’ ability to change preventive behaviors. The lack of a comprehensive conceptual synthesis limits the development of evidence-based strategies. This study aims to identify patterns of findings, research gaps, and theoretical implications regarding the role of social media campaigns in CSA prevention in Indonesia. The method used is a systematic literature review based on the PRISMA guidelines to ensure a transparent and structured process of literature identification, selection, and synthesis. Searches were conducted on Google Scholar, PubMed, DOAJ, SINTA, and national repositories. Of the 211 articles identified, 30 studies met the inclusion criteria and were analyzed based on research design, theoretical framework, campaign strategies, outcomes, and contextual factors. The synthesis results indicate that the literature is dominated by quasi-experimental and qualitative studies with limitations in testing causal relationships. Three main theoretical approaches were identified: behavior change theory, the social media engagement model, and the non-linear engagement framework. Although most studies reported increased knowledge and awareness, evidence of behavioral change remains weak and inconsistent. These findings reveal a conceptual gap between increased awareness and preventive actions, influenced by cultural factors, religiosity, platform characteristics, and messaging strategies. This study contributes by proposing an integrated theoretical framework linking social media engagement and behavioral change to explain the transition from awareness to CSA prevention actions.